Household Income Risk, Nominal Frictions, and Incomplete Markets - Ralph Lütticke; Christian Bayer; Lien Pham; Volker Tjaden (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper examines the effects of changes in uncertainty of household income on the macroeconomy. Households face substantial idiosyncratic income risk that is up to two orders of magnitude larger than total factor productivity uncertainty, very persistent and varies substantially over the business cycle. We build a New Keynesian model with heterogeneous agents, where changes in precautionary savings due to time-varying uncertainty depress aggregate activity. With countercyclical markups through sticky prices, increased precautionary savings lower aggregate demand and generate significant output losses as the economy is demand-driven in the short-run. The decline in output is more severe, if the central bank is constrained by the zero lower bound. Our results imply that household income uncertainty may be an important factor in explaining the persistent decline of consumption during the Great Recession.
Keywords: E21; E32; E58; 330